Dispersion of standard and non-standard lightning current to ground in a telecommunication building - Ahmad, H. (IEEE, 2007)
This paper describes on study about standard and non-standard lightning current dispersion system in telecommunication building by using ATP-EMTP simulation and structure model. The metallic grid like structure was modeled as multiphase Pi-circuit network, which consists of many mutually coupled branches and used to simulate the actual telecommunication building. ATP-EMTP simulation was used to validate the experimental test results obtained from 2 lightning protection system (LPS) model which are non-standards waveform in LPS Model A and standards waveform in LPS Model B. Data of lightning parameter in Malaysia from Lightning Detection System of Tenaga Nasional Research and Development for year 1995 were analyzed and several types of lightning current, voltage magnitude and shape were selected and applied to the simulation. This paper proves the usefulness in the utilization of EMTP in calculating the current distribution in a building during a lightning stroke for both types of current standard and non standard.